ELECTRON-ENERGY LOSS SPECTROSCOPY OF YBA2CU4O8 AND RELATED-COMPOUNDS - Yuan, J; Liu, R; Edwards, P; Browning, N; Brown, L (Elsevier, 1991)
O 1s and Cu 2p absorption in YBa2Cu4O8 are studied by transmission electron energy loss spectroscopy, and compared with results obtained from YBa2Cu3O7-δ (δ-0). The overall shapes of the spectra from two compounds are similar, reflecting a close similarity in their electronic and structural properties. The width of the empty states in the oxygen-dominated valence band is narrower in the YBa2Cu4O8 material, a result consistent with band structure calculations. Samples with nominal composition Y(Ba1-xSrx)2Cu4O8 are also investigated. For x ≤ 0.3, no significant change in the oxygen absorption edges is observed. For higher Sr doping levels, the change in the crystal structure and the reduction in the empty density of states in the valence band are found. The result is consistent with the Tc and X-ray diffraction measurements.